Quality of service and loyalty of consumer purchase in supermarkets and metro plaza real city Huánuco. 2013-2014 - Saquicoray Ávila, Pedro Pablo (2017)
Service quality is a complex concept that includes both tangible and intangible elements thatconsumers perceive to receive a service. Similarly, represents one of the most important variables informulating marketing strategies, which helps improve the competitiveness of the company. Loyaltyis another complex concept that allows knowing the intention or decision that takes the consumerto the service quality stimulus.Both concepts are closely related, as shown Heskett (1997) in their model of the Service ProfitChain, which is part of the essential information of companies, mainly services, to design strategiesand quality of service customer loyalty, which ultimately impact on its financial results. The research focused on establishing the partnership between the two concepts, quality of service and loyalty inHuanuco supermarket customers, considering their perceptions and behavioral intention.The methodology applied research corresponded to a quantitative cross-sectional study of descriptivecorrelational. The survey method was used to obtain information through a structured and validatedbased on the measuring of the questionnaire CALSUPER questionnaire. This was applied to a randomsample of 400 customers.The results of the research helped establish that there is a strong relationship between perceivedservice quality and customer loyalty purchase. Consumers in Huanuco supermarkets showed afavorable perception towards quality of service received, and high levels of loyalty, considering thewide range of these businesses. Service quality was measured in dimensions, physical evidence,political, personal interaction and reliability. Of these, the first two are the ones that are more relatedto loyalty as measured behavioral intention.Finally, it is recommended that management of supermarkets put greater emphasis on these twodimensions when defining aimed at improving service quality strategies, which will result in higherlevels of loyalty of existing and new customers.